HEC-RAS 2D Flood Modeling of Bango River: Developing Contextual Spatial Learning Media for Disaster Mitigation - Abdillah Hanafi; Didik Taryana; Rahmi Lailatur (Future Space: Studies in Geo-Education, 2026)
Geography education plays a pivotal role in building student resilience against disasters, yet learning materials often lack local contextualization. The Bango River in Malang City, which faces flooding every rainy season, presents a critical real-world context for such learning. This study focuses on processing hydrological data to create high-accuracy visualization models using a 2D hydraulic simulation in the HEC-RAS program. The discharge data used in this study was obtained from the calculation of the Synthetic Unit Hydrograph (HSS) Gama 1 method. The results of the hydrograph calculation served as input data for the inundation modeling. The peak discharge from the calculation of the HSS Gama 1 method obtained a value of 29.5825 m³/second. The modeling results show information about the affected buildings, the depth of flooding, and the extent of flooding around Pandanwangi Village. The simulation results indicate that for the 100-year return period, the total inundated area reaches 109.06 hectares. Beyond technical mitigation, these high-resolution inundation maps serve as crucial learning resources to enhance students' spatial thinking and disaster preparedness in local geography curricula. To mitigate future losses, appropriate anticipatory measures must be taken, including the integration of these spatial models into geography education to foster disaster-literate citizens.